CHAMPION OF SELOGIRI 2026: AJANG CERDAS CERMAT PELAJAR SEKOLAH DASAR - Muhammad Yunan Hidayat; Muhammad Taufik Nur Sapto Wardono; Alya Nur Fadlilah; Abdul Khaidir Halim (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
Education is one of the pillars of civilization and national progress. In this modern era, a developed nation is characterized by a high level of education, so every country competes to improve the education standard of its citizens. Education is essential not only at the individual level, but also globally. Indonesia, with a population of 286 million, is also racing to improve the standard of education. With the compulsory education program changed from 9 years to 12 years, it is hoped that this will be one solution in the form of education system reform, shifting the paradigm from mere schooling to learning (quality learning). The government continues to strive to optimize the education budget to support the compulsory education program, despite challenges in the equal distribution of facilities in various regions. Quiz is an academic quiz competition that tests knowledge, speed of thought, and teamwork in answering questions about disciplines such as science, social studies, mathematics, and general knowledge. This competition aims to improve literacy, critical thinking skills, and sportsmanship of students. This competition is held to improve the quality of education, motivate students to learn, and hone critical thinking skills and be quick and accurate in answering questions, self-confidence, and broaden academic and general insights among students.